Pemanfaatan Konten Digital Untuk Meningkatkan Daya Saing Dalam Agribisnis - Alamsyah, R. Yadi rakhman; Sardjono; Nurfalah , Mulki Zulkarnaen (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2025)
The use of digital technology in agribusiness is a crucial strategy to enhance efficiency, competitiveness, and market reach, especially for rural entrepreneurs. This Community Service Program aims to empower students at SMKN PP Lembang to utilize digital content for agribusiness promotion. The applied method includes pre-tests, counseling, mentoring, and evaluations using educational and hands-on approaches with multimedia applications such as Canva, CapCut, and Google Analytics. The results indicate improved knowledge and skills among students in producing engaging and professional digital content. Students also gained a better understanding of branding and digital marketing strategies through social media and online marketplaces. In conclusion, this program effectively enhances students’ digital agribusiness competencies and can serve as a sustainable empowerment model for vocational education communities in the agricultural sector.